1991
DOI: 10.1093/oxfordjournals.humrep.a137430
|View full text |Cite
|
Sign up to set email alerts
|

Granulated lymphocytes in human endometrium: histochemical and immunohistochemical studies

Abstract: Granulated lymphocytes with an unusual antigenic phenotype (CD56+ CD38+ CD2 +/- CD3- CD16-) form a substantial proportion of leukocytes in human endometrial stroma. The purpose of this study was to examine morphological and antigenic heterogeneity in endometrial granulated lymphocytes (eGL) in imprint preparations, paraffin-embedded sections and frozen sections. eGL in decidual imprints showed variations in cell size, nuclear size, shape and chromatin content and the number and size of cytoplasmic granules. eG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
346
1
6

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 511 publications
(365 citation statements)
references
References 0 publications
12
346
1
6
Order By: Relevance
“…This distribution was confirmed for pregnancy in phloxine tartrazine staining of pregnancy hysterectomies from 8 weeks to term ; granulated leukocytes were rare after 20 weeks gestation. Immunostaining for CD56 has largely confirmed this distribution, although CD56+ cells are present in the proliferative and early secretory phase, albeit in small numbers (Bulmer et al, 1991;King et al, 1989a). Numbers increase in the late secretory phase of the menstrual cycle and even higher numbers are observed in early pregnancy.…”
Section: Distribution Of Uterine Nk Cellsmentioning
confidence: 95%
See 2 more Smart Citations
“…This distribution was confirmed for pregnancy in phloxine tartrazine staining of pregnancy hysterectomies from 8 weeks to term ; granulated leukocytes were rare after 20 weeks gestation. Immunostaining for CD56 has largely confirmed this distribution, although CD56+ cells are present in the proliferative and early secretory phase, albeit in small numbers (Bulmer et al, 1991;King et al, 1989a). Numbers increase in the late secretory phase of the menstrual cycle and even higher numbers are observed in early pregnancy.…”
Section: Distribution Of Uterine Nk Cellsmentioning
confidence: 95%
“…In late secretory phase endometrium and early pregnancy decidua uNK cells are detected predominantly in the stratum functionalis, often forming aggregates around spiral arteries and glands (Bulmer et al, 1991). This perivascular distribution was considered by early workers to reflect diffusion of progesterone from blood into perivascular tissues.…”
Section: Trafficking From Blood or Local Differentiation Of Uterine Nmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] In humans, activation of uterine NK (uNK) cells has been genetically linked with fertility. In contrast, human infertility and gestational complications such as recurrent spontaneous abortion, intrauterine growth restriction and preeclampsia, are seen in specific maternal killer immunoglobulin-like receptors (KIRs) and fetal HLA-C gene combinations that evoke NK cell inhibitory signals.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely reported that in early human decidua most lymphocytes are CD%+CD16- (Starkey et al, 1988;King et al, 1989b;Bulmer et al, 1991b). Although some authors observed that most T cells were TCRaP + and few or none expressed TCRyG in this tissue (Chernyshov et al, 1993), others found a large number of TCRyG+ cells, but smaller numbers of TCRccP + cells (Mincheva-Nilsson et al, 1992).…”
Section: Discussionmentioning
confidence: 90%